Rancang Bangun Sistem Informasi Pelaporan Penyelenggaraan Pemerintahan Daerah (SIPPDA) Provinsi Nusa Tenggara Barat Berbasis Website: Design and Development of a Website-Based Reporting Information System for the Implementation of Regional Government (SIPPDA) for West Nusa Tenggara Province - Anisah Mutmainah; Nadiyasari Agitha; Royana Afwani (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2024)
The Government Office and Regional Development Agency (OTDA) have the main task of implementing regional autonomy by preparing the Regional Government Administration Report (LPPD). The preparation of LPPD for the NTB Province is still done manually, including the collection of data for each government affair and the calculation of government performance achievements found in various indicators, resulting in a lengthy data collection process for reporting. With the advancement of information technology, a solution can be provided to address the aforementioned issues by developing a web-based Local Government Administration Reporting Information System (SIPPDA) using the extreme programming development method. The system development is carried out using the Laravel framework. During the testing phase, unit testing is performed to verify the functionality of the system, and the results indicate that it runs smoothly without errors. User Acceptance Testing (UAT) is then conducted in three iterations with different numbers of respondents. In the first iteration, with 5 respondents, the acceptance rate is 73.71%. In the second iteration, with 8 respondents, the rate is 89.86%, and in the third iteration, with 5 respondents, the rate is 79.5%.